Depleted Mantle-sourced CFB Magmatism in the Jurassic Africa–Antarctica Rift: Petrology and 40Ar/39Ar and U/Pb Chronology of the Vestfjella Dyke Swarm, Dronning Maud Land, Antarctica - Luttinen, A.; Heinonen, J.; Kurhila, M.; Jourdan, Fred; Mänttäri, I.; Vuori, S.; Huhma, H. (Oxford University Press, 2015)
The Jurassic Vestfjella dyke swarm at the volcanic rifted margin of western Dronning Maud Land represents magmatism related to the incipient Africa–Antarctica rift zone; that is, rift-assemblage magmatism of the Karoo continental flood basalt (CFB) province. Geochemical and Nd–Sr isotopic data for basaltic and picritic dyke samples indicate diverse low-Ti and high-Ti tholeiitic compositions with εNd(180 Ma) ranging from +8 to –17. Combined with previously reported data on a subcategory of ferropicritic dykes, our new data facilitate grouping of the Vestfjella dyke swarm into seven geochemically distinct types. The majority of the dykes exhibit geochemical affinity to continental lithosphere and can be correlated with two previously identified chemical types (CT) of the wall-rock CFB lavas and are accordingly referred to as the CT1 and CT3 dykes. The less abundant Low-Nb and High-Nb dykes, a relatively enriched subtype of CT3 (CT3-E) dykes, and dykes belonging to the depleted and enriched ferropicrite suites represent magma types found only as intrusions. The chemically mid-ocean ridge basalt (MORB)-like Low-Nb and the depleted ferropicrite suite dykes represent, respectively, relatively high- and low-degree partial melting of the same overall depleted mantle (DM)-affinity source in the sublithospheric mantle.In contrast, we ascribe the chemically ocean island basalt (OIB)-like High-Nb dykes and the enriched ferropicrite suite dykes to melting of enriched components in the sublithospheric mantle. Geochemical modelling suggests that the low-Ti affinity CT1 and CT3, and high-Ti affinity CT3-E magma types of Vestfjella dyke may predominantly result from mixing of DM-sourced Low-Nb type magmas with <10 wt % of crust- and lithospheric mantle-derived melts. U/Pb zircon dating confirms synchronous emplacement of CT1 dykes and Karoo main-stage CFBs at 182·2 ± 0·9 and 182·2 ± 0·8 Ma, whereas two 40Ar/39Ar plagioclase plateau ages of 189·2 ± 2·3 Ma (CT1) and 185·5 ± 1·8 Ma (depleted ferropicrite suite), and a mini-plateau age of 186·9 ± 2·8 Ma (CT3-E) for the Vestfjella dykes raise the question of whether the onset of rift-zone magmatism could predate the province-wide c. 179–183 Ma main stage of Karoo magmatism. Notably variable Ca/K spectra suggest that younger 40Ar/39Ar plagioclase plateau ages of 173, 170, 164, and 154 Ma are related to crystallization of secondary minerals during the late-stage tectono-magmatic development of the Antarctic rifted margin. The occurrence of rare MORB- and OIB-like magma types in Vestfjella and along the African and Antarctic rifted margins suggests melting of geochemically variable depleted and enriched sublithospheric mantle beneath the Africa–Antarctica rift zone. Our models for the Vestfjella dyke swarm indicate that the voluminous lithosphere-affinity low-Ti and high-Ti rift-assemblage tholeiites could have been derived from MORB-like parental magmas by contamination, which implies sublithospheric depleted mantle as the principal source of the CFB magmas of the Africa–Antarctica rift zone.